2009
DOI: 10.2334/josnusd.51.373
|View full text |Cite
|
Sign up to set email alerts
|

Caries-preventive effect of glass ionomer and resin-based fissure sealants on permanent teeth: a meta analysis

Abstract: Abstract:The purpose of this quantitative systematic review was to appraise the evidence on the caries-preventive effect of glass ionomer cement (GIC) in relation to resin-based fissure sealants. Nine English and two Portuguese databases were searched (15 January 2008). Randomized clinical trials and systematic reviews were considered for inclusion. Trial exclusion criteria were: drop-out rates > 33%; no randomization; baseline differences in groups not statistically adjusted; and no clinically important outco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
85
0
3

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 96 publications
(91 citation statements)
references
References 30 publications
3
85
0
3
Order By: Relevance
“…Systematic reviews and meta-analyses have shown that both GIS and RS are capable of preventing the development of caries 5,6) . Nevertheless, the routine clinical use of a glass ionomer sealant is still unreliable because of poor retention 18) .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Systematic reviews and meta-analyses have shown that both GIS and RS are capable of preventing the development of caries 5,6) . Nevertheless, the routine clinical use of a glass ionomer sealant is still unreliable because of poor retention 18) .…”
Section: Resultsmentioning
confidence: 99%
“…The two most common materials used for sealing pits and fissures are resins and glass-ionomers. Systematic reviews and meta-analyses have shown that both glassionomer sealants (GISs) and resin-based sealants (RSs) are capable of preventing the development of caries 5,6) . The longevity of resin-based sealants is higher than that of low-and medium-viscosity glass-ionomer-based materials 7) ; however, glass-ionomer cement (GIC) is not as sensitive to moisture as resin-based sealants 8) .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The current literature on the preventive effects of sealants varies considerably. Some studies have reported that the anti-cariogenic effects of glass ionomer sealants are equal to those of resin sealants that do not contain fluoride 2,4,5) . Conversely, Mejare and Mjor reported that the preventive activity of glass ionomers surpassed that of the latter because of its greater capability to release fluoride 6) .…”
Section: Introductionmentioning
confidence: 99%
“…This suggests a therapeutic use for sealants in addition to a preventive use. Moreover, a systematic review through a meta-analysis indicated that GIC and RB fissure sealants were equally effective in caries prevention 9) . However, GIC offers mechanical properties and wear resistance that are inferior to composite resins [10][11][12][13] .…”
Section: Introductionmentioning
confidence: 99%